2018
DOI: 10.1097/md.0000000000009611
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of chidamide on relapsed refractory angioimmunoblastic T-cell lymphoma

Abstract: Introduction:Angioimmunoblastic T-cell lymphoma (AITL) is a kind of rare peripheral T cell lymphoma, which usually has acute onset at old age.Materials and methods:Here we report a case of relapsed refractory AITL, which has achieved obvious curative effect after treatment with chidamide.Results:Initially, the patient received 7 courses of treatment with recombinant human endostatin (endostar)+CHOP. The patient achieved complete remission, but suffered from recurrence later. After changing chemotherapy regimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…This large study demonstrates that chidamide has acceptable efficacy and safety profiles for relapsed and refractory PTCL patients [ 9 ]. In addition, Jin et al described a refractory AITL case who received chidamide with chemotherapy and achieved complete remission [ 10 ]. Chidamide combined with chemotherapy may be a new treatment for refractory and relapsed PTCL and ALTL patients.…”
Section: Discussionmentioning
confidence: 99%
“…This large study demonstrates that chidamide has acceptable efficacy and safety profiles for relapsed and refractory PTCL patients [ 9 ]. In addition, Jin et al described a refractory AITL case who received chidamide with chemotherapy and achieved complete remission [ 10 ]. Chidamide combined with chemotherapy may be a new treatment for refractory and relapsed PTCL and ALTL patients.…”
Section: Discussionmentioning
confidence: 99%
“…Chidamide is a novel orally histone deacetylase inhibitor (HDACi), which has inhibitory activity against HDAC1, 2, 3, 10 ( 26 ). It has shown activity against several types of tumors in vitro and in vivo ( 26 30 ). Chidamide might suppress T lymphoma cell growth and promote the apoptosis of T lymphoma cells though interfering with the binding between histone and DNA ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of chidamide and decitabine, a hypomethylating agent inhibited the growth of p300- or KMT2D-mutated T-lymphoma cells [ 16 ]. Moreover, clinical studies showed that chidamide had a favorable efficacy for angioimmunoblastic T-cell lymphoma [ 17 ] and relapsed/refractory peripheral T-cell lymphoma patients [ 18 , 19 ]. However, it has not been determined whether chidamide, either as a single agent or as a component of combined therapy, could induce autophagy in the rituximab/chemotherapy relapsed and refractory B-cell lymphoma cells.…”
Section: Introductionmentioning
confidence: 99%